PTH-025 Sniffing Disease? Optimisation of Sample Preparation for Volalite Organic Metabolomic Studies. (4th June 2013) - Reade, S; Sawbridge, D; Khalid, T; Probert, C
Abstract : Introduction: Colitis in both humans and rodents appears to alter the metabolome. Establishing the complete mouse faecal metabolome will aid studies of change in models of disease. The optimum method for such studies had not been described; we have optimised our sample preparation and developed a quantitative method. This will allow us to develop a mouse model that could potentially be translated for diagnoses and treatment in human disease. Methods: Optimisation was performed on 3, 5, 10 or 20 faecal pellets from C57BL/6 male mice (n = 4) and repeated 3 times. Volatile organic metabolite (VOM) profiles for each were analysed using SPME with a CAR/DVB/PDMS fibre and gas chromatography-mass spectrometry. This was done with careful control and monitoring of adsorption time (20 mins) and temperature (60°C) on the extraction yield during the assays. We also investigated the influence of acidification on the yield. The adsorption time of analytes in the fibre was studied testing 10, 20 and 30 minutes of extraction VOM from 10 pellets of mice faeces at 60°C. Results: ANOVA found a significant difference between sample of differing size; (p < 0.01); 10 and 20 pellets had most VOMs (37 and 44, respectively; NS); 10 pellets were used in later work (figure 1a). The addition of acid to faeces compared to untreated faeces produced similar chromatograms with slight increases in abundance and peak area of certain non-specific VOMs e.g. large chain organic acids (figure 1c). However, as this study aims to eventually determine disease biomarkers, at this point we do not want to influence the occurrence of specific VOMs from our samples. Varying the extraction time did not show any major differences in the quantity of VOMs identified between 10, 20 and 30 minutes, therefore our findings confirm what past literature using 20 minutes adsorption time have stated (figure 1b). Conclusion: We have optimised conditions for sample preparation to produce quantifiable and significant results. We are currently performing a longitudinal experiment on 6 male and 6 female C57BL/6 mice which will result in VOM profiles for each mouse along the time course of 8 weeks of a mouse's life, also providing us with 'normal' inter- and intra-animal metabolite variation. Such data will allow calibration of future studies of colonic disease in humans through the induction of colonic disease in mice. Disclosure of Interest: None Declared.